Cross-cultural Adaptation, Translation, and Validation of Gujarati Version of Neck Disability Index in Patients with Chronic Neck Pain - Shlesha Vaidya; Shreya Vaid (Archives of Medicine and Health Sciences)
Background and Aim: Specific to the population of Gujarat state, a need arises to have neck disability index (NDI) in the regional Gujarati language. The aim of present study is to translate NDI in Gujarati language and assess its validity for use in patient care. Materials and Methods: A total of 100 patients suffering from chronic neck pain and aged between 18 and 65 years participated in the study. In phase I, translation and cross-cultural adaptation of the original English version of NDI was performed according to the published guidelines. In phase II, all the patients were asked to complete a questionnaire booklet consisting of Gujarati version of NDI (NDI-G), Neck Pain and Disability (NPAD), and Beck’s depression inventory scales. The psychometric testing included evaluation of factor structure by exploratory factor analysis, reliability by test–retest reliability and internal consistency, agreement by Bland–Altman plots and value of measurement error (standard error of measurement and minimal detectable change), construct validity by assessing hypotheses of NDI-G correlations with the Gujarati version of Neck Pain and Disability (NPAD-G) and Gujarati version of BDI (BDI-G). A panel of 15 expert members assessed the content validity of NDI-G on a 7-point Likert scale for content equivalence, content relevance, and content representativeness. Test–retest reliability for the NDI-G was examined in 50 patients, twice with an interval of 48 h. Results: In phase I, the cross-cultural adaptation process of the NDI-G was successful, and less difficulty was experienced in achieving an acceptable translation. In phase II, the NDI-G showed strong psychometric properties. The translated version of the scale showed high internal consistency (Cronbach α = 0.82) and excellent test–retest reliability (Intra-class correlation coefficient = 0.982). Face and content validity of the NDI-G was well established with no floor and ceiling effects observed. In construct validity, convergent validity was confirmed by a high correlation of NDI-G with NPAD-G (r = 0.941, P < 0.01). Conclusion: The NDI-G was successfully translated into Gujarati, showing good psychometric properties. Its use is recommended for clinical and research purposes.